Defining metabolically healthy obesity in children: a scoping review. (28th August 2018) - Damanhoury, S.; Newton, A. S.; Rashid, M.; Hartling, L.; Byrne, J. L. S.; Ball, G. D. C.
Summary: We conducted a scoping review to identify definitions of metabolically healthy obesity (MHO), describe gaps in the literature, and establish a universal definition of MHO in children. We searched electronic databases from January 1980 to June 2017 and grey literature. Experimental, quasi‐experimental, or observational studies were eligible for inclusion if they (i) included a definition of MHO that identified risk factors, cut‐off values, and the number of criteria used to define MHO, and (ii) classified 2–18 year olds as overweight or obese. Two reviewers independently screened 1, 711 papers for relevance and quality; we extracted data from 39 individual reports that met inclusion criteria. Most (31/39; 79%) definitions of MHO included an absence of cardiometabolic risk factors. Heterogeneity across MHO definitions, obesity criteria, and sample sizes/characteristics resulted in variable prevalence estimates (3–80%). Finally, we convened an international panel of 46 experts to complete a 4‐round Delphi process to generate a consensus‐based definition of MHO. Based on consensus (≥ 80% agreement), our definition of MHO included: high density lipoprotein‐cholesterol > 40 mg/dl (or > 1.03 mmol/l), triglycerides ≤ 150 mg/dl (or ≤ 1.7 mmol/l), systolic and diastolic blood pressure ≤ 90th percentile, and a measure of glycemia. This definition of MHO holds potential universal value to enable comparisons between studies and inform clinical decision‐making for children with obesity.